THE ROLE OF THE “RIFIZOSTREP” PREPARATION IN THE PREVENTION OF BOVINE TUBERCULOSIS VETERINARY RESEARCH INSTITUTE TUBERCULOSIS LABORATORY - Mamadullaev G.H; Nabieva N.A.; Tuxliev A (Western European Studies, 2025)
In order to determine the effectiveness of the drug “Rifizostrep” in the treatment of tuberculosis, a series of experiments were conducted. As a result, on March 18, 2024, in the presence of the commission members, four calves in Group 1 were infected with M. bovis-149, and three calves each in Groups 2 and 3 were infected with the M. tuberculosis strain. After infection, Groups 1 and 2 received subcutaneous injections of the Rifizostrep preparation in the neck area once every 10 days according to the Methodological Guidelines. Group 3 served as the control group; after infection with M. tuberculosis-7880, no treatment was administered. As a result, when tuberculin testing was performed on the animals infected with M. bovis-149 and M. tuberculosis-7880 and treated with Rifizostrep (Groups 1 and 2), negative reactions were observed. In contrast, in the control group (Group 3), infected with M. tuberculosis-7880 but not treated with antibiotics, positive tuberculin reactions were recorded.
Keywords: cattle; Rifizostrep; preparation; strain